Healthcare at Your Fingertips: The Professional Ethics of Smartphone Health-Monitoring Applications. Issue 8 (17th November 2017) - Kwan, Vivian; Hagen, Gregory; Noel, Melanie; Dobson, Keith; Yeates, Keith
Abstract : Health professionals are inundated by the surfeit of health apps while lacking guidance to help them critically evaluate whether a particular health-monitoring app is safe, likely to lead to clinical benefit, and not introduce additional liability. Our objective is not to argue for or against the use of mobile health-monitoring apps but to illuminate the associated ethical issues and provide recommendations to guide the ethical decision-making process for clinicians who are considering the use of a mobile health-monitoring app. To this end, the Canadian Code of Ethics for Psychologists is used as a framework to situate recommendations.